Effectiveness of pain management among trauma patients in the emergency department, a systematic review. (May 2022) - Abu-Snieneh, Hana M.; Alsharari, Abdalkarem F.; Abuadas, Fuad H.; Alqahtani, Mohammed E.
Highlights: Analgesic treatment is an effective and ancient management strategy. New strategies reported and applied by oral or nasal route administration with similar and better efficacies. Nonpharmacological interventions may also contribute to pain relief. Abstract: Objective: To systematically review the available data and scientific literature and to compile all evidence-related studies of the effectiveness of pain management for traumatic patients in the emergency department. Methods: The present study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: A total of 777 articles were retrieved, and eighteen were selected according to the inclusion criteria in this systemic review. These studies were published from 2004 to 2020 and reported from all around the world. Seventeen studies were based on pharmacological intervention, and one study was based on nonpharmacological intervention. Analgesics and methoxyflurane administration were the most adapted interventions for pain management in traumatic patients among the selected studies. Other reported interventions were fixed nitrous oxide/oxygen mixture, sufentanil, and professional practice assessment. Conclusion: This systemic review provides an overview of the effectiveness of pharmacological and nonpharmacological pain management in trauma patients in the emergency department. Analgesic treatment is an effective and ancient management strategy with drawbacks of associated side effects and intravenous administration. New strategies reported and applied by oral or nasal route administration with similar and better efficacies. However, large-scale studies are crucial for better implementation and outcome. Nonpharmacological interventions may also contribute to pain relief.